Dermatology resident comfort level treating hair conditions related to patients with skin of color - Starling Tolliver, MD; Camilla Cascardo, MD; Nikita Wong, MD, MS; Yasmine Abushukur, MD; Geoffrey Potts, MD, FAAD (Wolters Kluwer, 2024)
Background:. Although recent studies demonstrated resident satisfaction in the treatment of skin of color (SOC) related disease, comfort levels treating hair specific to populations within the SOC spectrum is unclear. Objective:. The purpose of this study is to assess dermatology residents comfort level in recognizing and treating various common hair conditions with a focus on those specific to SOC. Methods:. An Institutional Review Board-approved survey was distributed to United States residents of Accreditation Council for Graduate Medical Education-accredited dermatology programs. Data pertaining to hair care knowledge and treatment comfort levels were collected. Analysis was completed using equal variance 2-sample t tests and analysis of variance F tests, P < .05. Results:. Dermatology residents were relatively comfortable with common conditions such as androgenetic alopecia and alopecia areata, but uncomfortable with creating healthy hair regimens, discussing natural hair care products, and treating trichorrhexis nodosa. Resident self-identification as underrepresented in medicine significantly impacted resident knowledge of hair care and treatment in patients with SOC. Limitations:. This study was limited due to small sample size and potential recall bias. Conclusion:. This study highlights knowledge gaps in understanding hair-related care for patients with SOC, affirming the continued importance of diversifying dermatology programs as well as hair-specific training for residents.